The lifelong socioeconomic disadvantage of single-mother background - the Helsinki Birth Cohort study 1934-1944 - H. Maiju Mikkonen; Minna K. Salonen; Antti Häkkinen; Maarit Olkkola; Anu-Katriina Pesonen; Katri Räikkönen; Clive Osmond; Johan G. Eriksson; Eero Kajantie (BMC, 2016)
Abstract Background Growing up with one parent is associated with economic hardship and health disadvantages, but there is limited evidence of its lifetime consequences. We examined whether being born to an unmarried mother is associated with socioeconomic position and marital history over the lifespan. Methods We analysed data from the Helsinki Birth Cohort Study including birth, child welfare clinic and school healthcare records from people born in Helsinki, Finland, between 1934 and 1944. Using a unique personal identification number, we linked these data to information on adult socioeconomic position from census data at 5-year intervals between 1970 and 2000, obtained from Statistics Finland. Results Compared to children of married mothers, children of unmarried mothers were more likely to have lower educational attainment and occupational status (odds ratio for basic vs. tertiary education 3.40; 95 % confidence interval 2.17 to 5.20; for lowest vs. highest occupational category 2.75; 1.92 to 3.95). They were also less likely to reach the highest income third in adulthood and more likely to stay unmarried themselves. The associations were also present when adjusted for childhood socioeconomic position. Conclusion Being born to an unmarried mother, in a society where marriage is the norm, is associated with socioeconomic disadvantage throughout life, over and above the disadvantage associated with childhood family occupational status. This disadvantage may in part mediate the association between low childhood socioeconomic position and health in later life.